Sport as a social phenomenon in professional training in Physical Education - Jocimar Daólio (Revista da Educação Física)
Regarding sport as a sociocultural phenomenon, its insertion in the curriculum for professional training in physical education is discussed in this paper refuting the exclusiveness of current technical dimension. A course that gives too much relevance to sport technical dimension won’t be training professionals able to consider the continuous change of sport modalities meaning by different human groups in the course of time. Instead of a course curriculum structured by sport modalities, this paper proposes that sport may be considered in three dimensions or moments. The “eyes training”, the sport pedagogy and the division into groups of modalities. It is intended to be a contribution to the training of physical education professionals so that they may work within a more critical and transforming perspective, and not only reproduce the technical dimension.